Enhanced Cuckoo Search Algorithm With Metaheuristic Components For Extracting The Maxima Of The Orientation Distribution Function - Shehab, Mohammad Mohammad Said (2018)
The Diffusion-Weighted Magnetic Resonance Imaging(DW-MRI) is a promising method for non-invasive investigation of anatomical connectivity in the human brain. The raw data acquired from the MRI scanner may not be directly usable by the specialists. Therefore, new methods are required to make more reasonable representations of the data to extract the required information from them. The initial representation of the MRI data is the huge groups of fibers. These fibers contain fiber crossing bundles, which link the functional brain areas all together as a complex net-work of neural fiber tracts. Q-ball imaging (QBI) is a Diffusion MRI reconstruction technique which has been proven very successful in resolving multiple intravoxel fiber orientations in MRI (i.e., fiber crossing) based on the standard computation of the Orientation Distribution Function (ODF), which is a 3- Dimension spherical function founded to detect the dominant fiber orientations in the underlying volume of a pixel (voxel).